A Comprehensive Study on Cellular Evolution from 1G to 6G - Mustari, Nazifa; Karabulut, Muhammet Ali; Shah, A. F. M. Shahen; Tureli, M. S. Ufuk (GAZI UNIV, 2025)
Due to the growing need for greater quality of service, data rates, capacity, and decreased latency, cellular communication is evolving. The design of cellular networks is being dramatically enhanced in order to meet these demands. The needs and demands are fulfilled due to new multiple access methods, modulation techniques, emerging technologies, etc. In this paper, a comprehensive study on cellular evolution from the first generation (1G) to sixth generation (6G) is presented. The cellular network designs, multiple access strategies, modulation techniques, and emerging technologies are considered in the study. The architecture of the cellular network is given from 1G to 5G. Some of the most important emerging technologies for improving architecture and meeting user demands are covered. Massive MIMO, software-defined networking, mmWave, and other upcoming technologies are among them. Additionally, several access mechanisms ranging from 1G to 5G are investigated. There is a comparison of several generations of cellular communication. The study also gives a preview of what the upcoming 6G may bring. There are obstacles and issues with 6G that are discussed.
Keywords: 5G; 6G; cellular network architectures; massive MIMO; mmWave; multiple access techniques; modulation techniques; WIRELESS COMMUNICATIONS; INDEX MODULATION; FUTURE; SYSTEMS; INTELLIGENT; CHALLENGES; NETWORKS; VISION; REQUIREMENTS; BLOCKCHAIN; Engineering